Cardiovascular disease in systemic sclerosis - an emerging association? - Ngian, Gene-Siew (BioMed Central, 2011)
Microvascular disease is a prominent feature of systemic sclerosis (SSc) and leads to Raynaud's phenomenon, pulmonary arterial hypertension, and scleroderma renal crisis. The presence of macrovascular disease is less well established, and, in particular, it is not known whether the prevalence of coronary heart disease in SSc is increased. Furthermore, in terms of cardiac involvement in SSc, there remains conjecture about the relative contributions of atherosclerotic macrovascular disease and myocardial microvascular disease. In this review, we summarize the literature describing cardiovascular disease in SSc, discuss the pathophysiological mechanisms common to SSc and atherosclerosis, and review the surrogate markers of cardiovascular disease which have been examined in SSc. Proposed mediators of the vasculopathy of SSc which have also been implicated in atherosclerosis include endothelial dysfunction, a reduced number of circulating endothelial progenitor cells, and an increased number of microparticles. Excess cardiovascular risk in SSc is suggested by increased arterial stiffness and carotid intima thickening and reduced flow-mediated dilatation. Cohort studies of adequate size are required to resolve whether this translates into an increased incidence of cardiovascular events in patients with SSc.